Surveillance of Communicable Disease Incidence of Diarrhea in The Working Area of Puskesmas Samarinda Kota - Farah Aulia; Anifa Temongmere; Aurangelica Pascalia (Universitas Mulawarman, 2026)
Diarrhea is one of the non-communicable diseases in Indonesia with a considerably high incidence rate, particularly among vulnerable age groups. This study aimed to analyze the implementation of surveillance on communicable disease incidence, namely diarrheal disease, in the working area of Puskesmas Samarinda Kota. This study used a descriptive quantitative survey design, conducted in May 2025 in Kelurahan Bugis, Kecamatan Samarinda Kota. A total of 30 respondents were selected using purposive sampling technique. Data were collected through direct questionnaires and processed using IBM SPSS Statistics software. The results showed that 50% of respondents were toddlers, 96.7% had watery stools, 53.3% defecated more than four times per day, and 96.7% experienced sudden onset of diarrhea. All respondents used packaged water as their drinking water source, 96.7% used tap water (PDAM) for daily needs, 60% had habits of eating outside the home, and 80% lived in densely populated alleyways. A total of 86.7% of respondents sought care at health facilities, predominantly at Puskesmas Samarinda Kota (73.3%). Diarrhea in the working area of Puskesmas Samarinda Kota remains a major public health problem, particularly among toddlers, with poor environmental sanitation and the habit of eating outside the home as the main risk factors.